Paces: A Primary Care Tool to Detect Mental Health Disorders in Indigenous Colombians - Rojas-Andrade, R (James Cook University, 2023)
Introduction: The aim of this research was to present the process of intercultural creation and validation, in addition to the analysis of the psychometric properties of the Parenting, Behavior, Emotions and Suicide risk scale. Methods: A cross-sectional study, cultural adaptation and validation with an ethnic approach were carried out by expert judges in mental health; subsequently, the instrument was applied, and a factorial analysis was carried out, and it was established that there was agreement between the instrument results and two expert perspectives regarding spiritual disharmony. The sample consisted of 168 families of children and young people (54.8% women, 45.2% men), with a mean age of 11.2 years, in Colombia. Regarding the geographical location, 44% were from Guajira, 44.6% were from Nariño and 11.3% were from Vaupés, from the Wayuu, Awá and Emberá communities, respectively. Results: The scale showed high reliability (Chronbach’s α=0.911), and in the factorial analysis the following parenting domains were formed from the parents: involvement, monitoring and bond, from boys, girls and young people; suicidal risk perceived by caregivers and perceived by children and young people; in addition to a total mental health risk. The questions that inquired about hallucinations and seizures did not show grouping in any factor, and two questions were eliminated. Similarly, a high inter-rater concordance was shown, with a higher Cohen’s κ coefficient for all domains. Conclusion: There are few intercultural and early detection studies of parenting and mental health problems in children and youth that have an ethnic approach. It is observed that the instrument serves as a means of monitoring mental health issues in children and adolescents, as well as the parenting practices employed in their socialization, from both the perspective of caregivers and the young individuals themselve. This study indicates that the scale is an adequate tool, quick and easy to administer in first-level care settings. © (2023), (James Cook University). All Rights Reserved.